OPTIMIZATION OF METHANE PRODUCTION FROM CRUDE GLYCEROL DERIVED OF BIODIESEL PRODUCTION FROM WASTE COOKING OIL - Mello, Bruna [UNESP]; Pozzi, Arthur; Rodrigues, Brenda Clara Gomes [UNESP]; Sarti, Arnaldo [UNESP] (My University, 2022)
Biogas production from wastes and residues is a very promising option for renewable energy production. In this study, glycerol generated in biodiesel production from waste cooking oil was used as a sole organic source for biogas production. Optimization of the factors that influence the anaerobic digestion of crude glycerol was performed by a factorial central composite design with two variables (food to microorganism ratio and batch time) at five levels and the specific methane production was the response variable. The results showed that F/M ratio of 2.04 gCOD/gVS and a batch time of 5 days reached the highest specific methane production of 46 NmLCH4/gVS. The desirability function revealed that the optimal conditions related to the maximum methane production were a batch time of 6 days while the ideal F/M ratio was not achieved in the interval evaluated. Also, the mathematical model proposed in this study can be used to estimate the specific methane production from crude glycerol.
Keywords: Anaerobic Digestion; Central Composite Design; Desirability Function; Modeling; Specific Methane Production